Digital agriculture technology adoption in low and middle-income countries—a review of contemporary literature - Manzoor, Faiza; Wei, Longbao; Siraj, Mahwish; Lu, Xueqin; Qiyang, Guo (Frontiers in Sustainable Food Systems, 2025)
The use of digital technology in low- and middle-income countries (LMICs) is shaped by multiple factors that can enable or hinder adoption. Understanding these factors is crucial, as LMICs face many constraints that limit the benefits of digital innovation. Therefore, this paper thoroughly evaluates the literature to identify the key determinants influencing the adoption of digital agriculture technologies in LMICs. A total of 30 relevant publications, dated between 2019 and May 2025, were retrieved from the academic databases Google Scholar, Scopus, and Web of Science through a systematic search and analysis approach with clearly defined inclusion criteria to ensure relevance and comparability. This study highlights that socioeconomics, agro-ecological, technological, institutional, situational, social, and behavioral factors are the most frequently discussed influences on digital agriculture technology adoption. Nonetheless, only a few studies have examined all of the components of the complex adoption process, and the majority were only concerned with assessing the impact of a single factor. The findings suggest that these factors positively influence the adoption of digital agriculture technologies, but their effects vary across contexts. The study recommends that policymakers, practitioners, and development agencies adopt integrated strategies that address multiple barriers simultaneously to enhance the uptake and sustained use of digital agriculture technologies.